The role of the us supreme court in the legal system (Journal of actual problems of jurisprudence, 2021)
The purpose of the article on the topic of judicial lawmaking in the USA, which attempts to invade the educational process and intensify the study of the History of State and Law of Foreign Countries, is devoted to the U.S. Supreme Court – the founder of constitutional justice and one of the pillars in the system of separation of powers. This is a unique judicial institution with an exceptional degree of influence, about which America’s famous political writer Alexis do Tocqueville stated that “never before have any people had such a powerful judicial authority”. The purpose of the research is to identify the features of the law-making activity of the US Supreme Court, since judicial law making in science remains an unsolved problem. To achieve this goal, the methods of scientific research were used, in the form of general methods, complex special methods of jurisprudence. For the reader, the phenomenon of the us Supreme Court is interesting in several aspects. First, from the point of view of the evolution of American law and the judicial system in all its dynamics and contradictions. Secondly, in terms of the implementation of judicial activity, complex thought processes of finding the necessary precedents and arguments in a particular case, achieving (if possible) a compromise between the judges-colleagues. Judicial activity should be interpreted not only as based on law, but also subject to ideological and political influences. The results of the research are very important for researchers of the legal system of foreign countries, and to look at the us Supreme Court through the eyes of American history as an institution that has the potential to enter into conflict with both the legislative and Executive authorities. On the other hand, it is important to understand the logic of filling vacancies in the Supreme Court by the Executive branch. In the ongoing in this country, searches the reasons for negative political and legal phenomena attention is drawn to the interpretation of the Federal Constitution, the U.S. Supreme Court, in General, the activities of the court performing a legislative function, it is unusual and constitutional loose. However, many issues remain insufficiently studied, including the role of the US Supreme Court in constitutional law making, and the phenomenon of judicial law making itself. Key words: lawmaking, jurisdiction, Supreme Court, USA, legislature.